Early Career English Teachers' Performance: Stories and Challenges in Enhancing Students’ Language Proficiency - Saqifanty, Awanda Bramantika; Sakhiyya, Zulfa; Widhiyanto (Universitas Negeri Semarang, 2025)
Teachers’ determination of effective teaching methods to enhance English proficiency in primary schools has become an urgent concern. English has become one of the mandatory subjects again for all primary schools, especially public primary schools, have to start from third to sixth grade. In reality, a lot of public primary school students find it challenging to gain proficiency in the language, which limits their capability to engage completely in the school. This research aims to delve into how early career English teachers navigate teaching and learning process in English class, the challenges and opportunities for early career English teachers in implementing teaching methods, and students’ perception of early career English teachers’ performance in enhancing students’ English language proficiency. This qualitative research study employs a case study as methodology. The study used observations, interviews, and questionnaires to collect data from each early career English teachers in SDN Kupang 02, SDN Tambakboyo 02, and SDN Bandungan 03 as public primary schools in Semarang Regency. The results demonstrate that early career English teachers' teaching methods affected students’ English proficiency. Using creative and interactive learning media can create an enjoyable, engagement, and conducive English class. It beneficially affected in enhancing student’s English language proficiency.